Embracing Core Values: Finding Joy in the Challenges of our Work. Issue 153 (March 2016) - Roper, Larry D.; Porterfield, Kent T.; Whitt, Elizabeth J.; Carnaghi, Jill E.
Abstract : This chapter describes and discusses implications of the experiences of student affairs leaders—the challenges and the opportunities, the obstacles and the joy—for understanding and facilitating student affairs leadership.